O novo basquetebol brasileiro : um olhar sobre os processos de formação e de espetacularização da modalidde no país - Mellini, Felipe (2016)
The dissertation here presented describes and analyzes the process of the establishment of the Liga Nacional de Basquete (National Basketball League), in addition to investigating the proposal to restructure basketball in the country by means of the creation of the first domestic professional sports league to be managed by clubs themselves. The professionalization of the game in Brazil, undertaken according to the logic of sport-spectacle, is here discussed in particular, using as reference two ethnographic experiences, the first in a game organized by the National Basketball Association (NBA) and taken place in Brazil, in the city of Rio de Janeiro, and the second in a Novo Basquete Brasil game taken place in Franca, in the state of Sao Paulo, a city known as the capital of Brazilian basketball